2008
DOI: 10.1088/0268-1242/23/3/035023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of defects in semiconductors on reproducibility and performance of thin-film photovoltaic solar cells

Abstract: Thin-film solar cells based on GaAs/Al x Ga (1−x) As showing open circuit voltages of (1100-1170) mV and fill factors of (0.80-0.87) have been exposed to external electrical stresses, and current-voltage characteristics were monitored in order to study the effects of defects present in the device structure. It has been found that peculiar kinks, sudden jumps and various deformations occur in current-voltage curves which could be caused when the Fermi level moves position at the device interface. These changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…In references [18] and [19], similar instabilities of GaAs/ AlGaAs graded bandgap, lab-scale devices were reported.…”
Section: Solar Cells Based On Gaas/algaassupporting
confidence: 52%
See 2 more Smart Citations
“…In references [18] and [19], similar instabilities of GaAs/ AlGaAs graded bandgap, lab-scale devices were reported.…”
Section: Solar Cells Based On Gaas/algaassupporting
confidence: 52%
“…The aim of this review paper is to share main author's similar experiences with devices based on commercially established inorganic semiconductors like cadmium telluride (CdTe), gallium arsenide and its aluminium alloy (GaAs/ AlGaAs) and copper indium gallium di-selenide (CuInGaSe 2 or CIGS). Authors summarise their experimental results observed and reported in the literature [17][18][19], and explain these variations with the effects of electronic defects. Instead of ionic migration and polarisation affects the behaviour of these I-V characteristics, the phenomenon is described in terms of slow "trapping" and "de-trapping" of charge carriers in defects within the materials and the device structure.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the case of thin film solar cells, material layer thicknesses are in nm region, and therefore seriously affected by defects. This is where strong "Fermi level pinning" takes place as reported in the past [17][18][19]. Hence, when trying to describe these "non-ideal" systems, it is more appropriate to use the Fermi level as the reference energy level.…”
Section: Discussion Of Perovskite Solar Cellmentioning
confidence: 97%
“…The technical issue of photovoltaic equipment is still a key factor in comprehensive efficiency improvement. The energy efficiency ratio will be comprehensively improved by decreasing the loss of the current transformer, optimizing the transformation efficiency of photovoltaic array and enhancing the overall efficiency of inverter [18,19]. In addition, Chiu and Chang conclude that the condition of photovoltaic equipment, the load situation of photovoltaic power generation system, operation capability and control level are also key factors that influence the comprehensive efficiency of photovoltaic power generation [20,21].…”
Section: Literature Reviewmentioning
confidence: 99%